LncRNA2Target: a database for differentially expressed genes after lncRNA knockdown or overexpression. Issue Volume 43:Issue D1(2015) (15th November 2014) - Jiang, Qinghua; Wang, Jixuan; Wu, Xiaoliang; Ma, Rui; Zhang, Tianjiao; Jin, Shuilin; Han, Zhijie; Tan, Renjie; Peng, Jiajie; Liu, Guiyou; Li, Yu; Wang, Yadong
Abstract : Long non-coding RNAs (lncRNAs) have emerged as critical regulators of genes at epigenetic, transcriptional and post-transcriptional levels, yet what genes are regulated by a specific lncRNA remains to be characterized. To assess the effects of the lncRNA on gene expression, an increasing number of researchers profiled the genome-wide or individual gene expression level change after knocking down or overexpressing the lncRNA. Herein, we describe a curated database named LncRNA2Target, which stores lncRNA-to-target genes and is publicly accessible at http://www.lncrna2target.org . A gene was considered as a target of a lncRNA if it is differentially expressed after the lncRNA knockdown or overexpression. LncRNA2Target provides a web interface through which its users can search for the targets of a particular lncRNA or for the lncRNAs that target a particular gene. Both search types are performed either by browsing a provided catalog of lncRNA names or by inserting lncRNA/target gene IDs/names in a search box.